2021
DOI: 10.1063/5.0054606
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the first and second attenuation zones in seismic metasurface

Abstract: Semi-infinite elastic metamaterials and metasurfaces on homogeneous elastic halfspaces have attracted significant attention in the past two decades as efficient artificial structures to control and mitigate surface waves. In this research, the first two attenuation zones of an elastic metasurface composed of different arrangements of pillars on a substrate are investigated. First, the lowest-frequency attenuation zone (LFAZ) is numerically investigated. Then, the rainbow trapping effect of the second attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Theoretically, the depth of the half-space should be infinitely deep. In order to facilitate simulation calculations and obtain relatively accurate convergence results, the depth of the soil substrate is selected as H = 500a [42,47]. A part of the spring is replaced by a thin rubber layer with thickness of t1 to achieve bandgaps at lower frequencies.…”
Section: Results and Discussion Of The Smsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the depth of the half-space should be infinitely deep. In order to facilitate simulation calculations and obtain relatively accurate convergence results, the depth of the soil substrate is selected as H = 500a [42,47]. A part of the spring is replaced by a thin rubber layer with thickness of t1 to achieve bandgaps at lower frequencies.…”
Section: Results and Discussion Of The Smsmentioning
confidence: 99%
“…In addition, for better integration of SMs in the foundation of a building for seismic isolation purposes, Yan et al [35] proposed a 2D periodic foundation constituted of ductile cast iron, supper soft rubber and reinforced concrete, while Casablanca et al [36] designed a periodic mass-in-mass foundation placed underneath buildings. To obtain wider bandgaps, the pillars with different kinds of structures [28,[37][38][39][40][41][42], and the "rainbow trapping effects" [8,29,34,[43][44][45][46][47] were utilized. However, the ultra-low-frequency (< 2 Hz) bandgaps are hard to obtain by using small-size structures.…”
Section: Introductionmentioning
confidence: 99%
“…Flexural seismic metasurfaces are currently much less studied than their counterparts composed of arrays of elastic rods bars or mass-spring resonators transmitting longitudinal vibrations, see for example [3,11,18,19]. These 'metasurfaces', motivated by experimental results of real life seismic systems [2], have consistently been demonstrated to produce significant band gap effects for surface waves in a variety of media [9,13,20], with potential applications in wave suppression and energy harvesting [1].…”
Section: Introductionmentioning
confidence: 99%
“…If the advantages of both can be exploited, it will be possible to contrive MMBs with ultralow-frequency and ultra-broadband wave attenuation capabilities. Recently, experimental results have shown that coupling FBG and SBG can create wider Rayleigh wave attenuation, where the distance between the different bandgaps is critical [ 72 ]. In the latest research on the introduction of strong nonlinearity into resonators arranged on free surfaces, the dispersion of low- and higher-order harmonics spreading through the metasurface has been found, which provides an opportunity to broaden the bandgap, but it is still difficult to reduce the effective frequency to an ultralow level [ 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%